2018
DOI: 10.1371/journal.pone.0199310
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to elevated glucose concentrations alters the metabolomic profile of bovine blastocysts

Abstract: Chronically high blood glucose concentrations are a characteristic of diabetes mellitus. Maternal diabetes affects the metabolism of early embryos and can cause a delay in development. To mimic maternal diabetes, bovine in vitro fertilization and embryo culture were performed in fertilization medium and culture medium containing 0.5, 2, 3, and 5 mM, glucose whereas under control conditions, the medium was glucose free (0 mM). Compared to control conditions (0 mM, 31%), blastocyst development was decreased to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 54 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…Interestingly, maltose has been shown to inhibit the binding of bovine and porcine spermatozoa to oviduct epithelial cell carbohydrates, a process allowing sperm storage and the delivery of capacitated spermatozoa to the site of fertilization [44,45]. The low levels of sources of glucose in oEVs in the post-ovulatory period are also concordant with the fact that exposure of the early bovine embryo to high amounts of glucose in vitro disturb embryo development and metabolism [46,47].…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, maltose has been shown to inhibit the binding of bovine and porcine spermatozoa to oviduct epithelial cell carbohydrates, a process allowing sperm storage and the delivery of capacitated spermatozoa to the site of fertilization [44,45]. The low levels of sources of glucose in oEVs in the post-ovulatory period are also concordant with the fact that exposure of the early bovine embryo to high amounts of glucose in vitro disturb embryo development and metabolism [46,47].…”
Section: Discussionmentioning
confidence: 97%
“…Many studies reported that fatty acids are ligands for PPARs to transcribe genes for mitochondrial fatty acid oxidation, and PPAR inhibition reduces fatty acid oxidation as well as lipolysis [8,42]. Furthermore, elevated concentrations of non-esterified fatty acids and glucose enhance lipid contents and reduce lipolysis and fatty acid β-oxidation [43,44]. Increased lipid contents were correlated with apoptosis in blastocysts [38].…”
Section: Discussionmentioning
confidence: 99%
“…We could not elucidate the effects of glucose and albumin levels on the embryo recovery rate after multiple superovulations with AI, but we proved that glucose level affects embryonic development in vitro . A high glucose concentration in the embryo culture media deleteriously affected the blastocyst developmental rate compared with a low glucose concentration in bovine [ 30 ] and mouse [ 31 ]. Bovine serum albumin contains numerous amino acids, and the addition of albumin to a culture medium has a positive effect on embryonic development in vitro [ 32 ].…”
Section: Discussionmentioning
confidence: 99%